Implementation of Reading Method Using Letter Puzzles to Increase Interest in Learning to Read in Students at RA Ar Rohmah Suren - Hotimah; Karlina, Herlin (MANDAILING GLOBAL EDUKASIA, 2025)
Reading is important in children's development. This ability is very necessary for children's readiness to reach the next level of education. However, this is often a benchmark for parents to make their children good at reading even though the child is not ready to accept it. Based on the limitations of the problem that the researcher has stated above, the existing problem can be formulated as